Talent Management in the Tourism and Hospitality Industry: Evidence from Iran. Issue 1 (2nd January 2020) - Bagheri, Moslem; Baum, Tom; Ebrahimi, Abolghasem; Abbasi, Abbas
ABSTRACT: This study investigates the notion of talent in the tourism and hospitality (TH) industry, proposing a comprehensive talent management (TM) model that is specific to this industry. This study primarily explores the notion of talent, TM, and the importance of these in the industry. A mixed method approach (qualitative and quantitative) was used to fulfill the research objectives. Qualitative content analysis was used to address interview responses from a panel of experts and a survey method was applied to collect data from a wider industry population through questionnaires. The data collected were analysed in SPSS and LISREL. Based on the findings, a model is proposed for talent definition in the Iranian TH industry.